PENYULUHAN KESEHATAN TENTANG KARIES GIGI DAN LOMBA GOSOK GIGI DI WILAYAH RT 08 KELURAHAN MURNI - Mira Andani; Robby Hardian; Win Fadillah; Vevi Suryenti Putri; Maimaznah Maimaznah (Sekolah Tinggi Ilmu Kesehatan Baiturrahim Jambi, 2019)
Damage of teeth can be affect for health of the other body, so it will interfere with daily activities. Based of the assessment in 26 school-age children in RT 08 Kelurahan Murni, showed 20 people (76.92%) who had tooth holes and black teeth, even though 18 people (69.23%) had brushed their teeth twice a day . Therefore, it is necessary to conduct health education on dental caries and tooth brushing competitions accompanied by demonstrations so that children can find out how to brush their teeth properly to avoid dental caries. The target of this counseling is that school-age children can practice the correct way of brushing their teeth to prevent dental caries. Extension activities were carried out for 45 minutes with the stages of directing participants to the place to be counseled, opening the presentation delivered by the moderator, delivering counseling material delivered by the presenter, demonstrating how to brush teeth properly, directing children to take part in brushing competitions, conducting competitions brush your teeth, give gifts to children who can brush their teeth properly, evaluate the counseling participants, distribute leaflets to the audience, document activities. The results of counseling activities are children are able to do the right way to brush their teeth.